Value Consistency in Peace Journalism: Opposing Structural and Cultural Violence through Prodding for Positive Peace. Issue 4 (8th August 2022) - Perry, Stephen D.
ABSTRACT: The father of peace studies addressed more nuances in the progress toward peace than journalism scholarship has applied to date. One problem has been emphasizing direct violence over cultural and structural violence. This essay questions the assumption that all parties in a conflict should be treated equally, suggesting that journalists judge motivations ranging from selfish to philanthropic. Philosophies of just peace and just war provide a series of questions to prompt variation in scholarly assessment of conflict situations. Journalists are encouraged to create tension against cultural and structural violence using a proposed framework to promote an enduring equanimous peace.